PENYULUHAN INFEKSI SALURAN PERNAFASAN AKUT (ISPA) DI PUSKESMAS UPTD TANAH TINGGI TAHUN 2024 - NINGSIH SAFARI, FIFI RIA; Bestari Sinaga, Eliza (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2024)
The problem of ARI (Acute Respiratory Infection) tends to increase in the last few decades both globally and nationally. ISPA is an infectious disease that causes the main cause of mortality and morbidity in the world. In 2022, the estimated number of pneumonia cases in children under five will be around 949 cases, and of this estimated number, 2 cases of pneumonia were found in children under five years old or around 0.2%. Data obtained from the Tanah Puskesmas UPTD Working Area High in 2024, there will still be many cases of ISPA so handling needs to be done optimally. The activity was carried out at the Tanah Tinggi Community Health Center UPTD on 28 and 29 November 2024 at 10.00 WIB and was attended by 19 mothers. There is a need to increase education and health promotion with various efforts such as utilizing social media trends as well as print and electronic media to make it easier for students to understand more about ISPA prevention behavior.